Does Financial Inclusion Affect Banks Profitability? Empirical Evidence from The MENA Region - Sahraoui Jalila; Abduallah Alfadli; Bentouir Naima (Journal of North African Economies, 2025)
This study seeks to examine the influence of financial inclusion on the banks’ profitability in the MENA region. Using an econometric analysis, namely (GMM), using 79 banks as a sample, covering the period (2011-2021). We assessed financial inclusion by utilizing three indicators: the number of ATMs, the number of bank branches, and the number of bank depositors. Additionally, we evaluated the bank's profitability by considering two indicators: return on average assets and return on average equity. The findings indicate a noteworthy and favorable influence of ATMs and BRAN on the banks' profitability as measured by ROAA- ROAE. However, there is no discernible impact of DEPO on the banks' profitability, thus verifying our hypothesis 1-2. The results validate the notion that improving financial inclusion has the potential to boost the bank's profitability in MENA countries.